Genome copy number feature selection based on chromosomal regions alterations and chemosensitivity subtypes - Vargas Amador, Josue (2018)
Cancer disease causes millions of deaths throughout the world and thousands in Costa Rica, and cancer treatment causes an immense economic burden on the social security system because drugs against the disease are extremely expensive. Through DNA sequencing techniques, the copy number of each gene could be found in order to describe how many times a gene is repeated within chromosomes. This type of data is of great importance since the cancer manifests a phenomenon called aneuploidy that consists of alterations in the number of chromosomes copies. Theories about the importance of aneuploidy in cancer supposed this phenomenon is a evolutionary engine that allows the disease to grow and resist changes produced by the organism and the treatments applied to these tissues. Studies have collected data on the number of copies in well-known databases such as CCLE and TCGA, which can be used to analyze the relationship between alterations in DNA and resistance to chemotherapies. In this study as a contribution, it was proposed to use statistical pattern recognition methods in order to identify chromosomal regions of DNA related to cancer chemosensitivity subtypes (resistant and sensitive subgroups) and then use these regions for CCLE cell lines labeling and TCGA samples classification.